Analisis Tingkat Kebisingan di Kamar Mesin Kapal MT. Suchaonugnum Serta Pemilihan Peredaman - Wa’addulloh, Mu’izzaddin; Purwanto, Purwanto (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
Noise can be defined as a sound or noise that can disturb comfort and health and can cause deafness. Noise that occurs continuously with high intensity can unconsciously affect the health of the Crew (ABK) who are on duty on the ship. Health problems can occur because the ABK are required to be in the ship's engine room which can last a very long time according to the route of the ship's voyage. This study aims to determine and analyze the noise in the engine room and accommodation room on the ferry. The data analysis technique used in this study is noise measurement and analysis of measurement data. The results of the study showed that there was 1 room on the MT. Suchaonugnum ship that did not meet the standards of the Indonesian Classification Bureau and MSC.337(91), including the engine control room. The highest noise source produced in the engine room is produced by the auxiliary engine. While in the lounge room, passenger accommodation room and VIP Room the highest sound source is produced by the sound system. The sound system that is always turned on when the ship is operating is one of the sources of noise that makes the noise level in the passenger accommodation room not in accordance with the MSC.337(91) standard because the sound pressure is too high. The noise level in the passenger accommodation space can be overcome by reducing the sound pressure on the sound system.